Natural Hydrogels, the Interesting Carriers for Herbal Extracts. (1st November 2022) - Fathi, Milad; Ahmadi, Nadia; Forouhar, Ali; Hamzeh Atani, Saied
ABSTRACT: Hydrogels with unique 3D networks and the stimuli-responsive feature can act as smart carriers of different bioactive compounds such as herbal extracts. While herbal extracts have abundant health benefits, sensitivity to environment and process conditions, limit their applications. Encapsulation in hydrogel not only protects them from external adverse effects but also provides controlled release behavior. This review focuses on important aspects of hydrogels, including classification and production techniques involving chemical and physical methods with highlighting natural hydrogels which are more preferably in the food industry, stimuli-responsive behavior, release mechanisms of active compounds, and their biological fate.